The Relationship Between Dietary Patterns and Type 2 Diabetes Mellitus Patients in the Working Area of ​​Gerunggang Community Health Center, Pangkalpinang City - Masagus Hakim; Taufik Kurrohman; Dedek Sutinbuk (Gayaku Publisher, 2025)
Background: The chronic disease known as type II diabetes mellitus is characterized by the body's inability to properly produce or use insulin. Diet is one element that causes high blood sugar in people with type II diabetes, which makes meal planning and dietary choices essential for managing blood sugar levels. Maintaining a healthy diet is vital in effectively managing type II diabetes mellitus. The suggested dietary plan for individuals with type II diabetes needs to take into account the 3Js: food type, food portion sizes, timing of meals, and a balanced caloric intake. Objective: This study aims to investigate the relationship between eating habits in individuals with type II diabetes mellitus within the area served by the Gerunggang Community Health Center in Pangkalpinang City. Method: This research employed a correlational framework utilizing an approach that is cross-sectional. Simple random sampling was used as the sample technique. 414 people made up the study's total population, of whom 91 participants from the Gerunggang Community Health Center neighborhood of Pangkalpinang City had type II diabetes mellitus. Results: The study's findings demonstrated a significant correlation between type II diabetes mellitus patients' food type (p value = 0.011 < α = 0.05), food quantity (p value = 0.003 < α = 0.05), meal schedule (p value = 0.083 < α = 0.05), and the role of family support (p value = 0.001 < α = 0.05). Conclusion: The results of this study show that the dietary practices of people with type II Diabetes Mellitus are related to the type of food consumed, the amount consumed, the time of meals, and the impact of family support.